Analisis Penggunaan Metode Capital Asset Pricing Model Dalam Pengambilan Keputusan Investasi Saham: Analisis Penggunaan Metode Capital Asset Pricing Model Dalam Pengambilan Keputusan Investasi Saham - fakhirah, zahra; Fitriani Komara, Esi (Advantage: Journal of Management and Business, 2024)
This research aims to determine the conditions of returns, risks, and the categorization of efficient and inefficient stocks in the property & real estate sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The population of this study consists of 45 property & real estate sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sampling technique used is purposive sampling based on predefined criteria, resulting in a sample of 41 companies. The method employed in this research is a quantitative and associative approach. The data analysis technique involves using the CAPM method, which includes calculating the actual return rate (Ri), market return rate (Rm), risk-free rate (Rf), beta value of stocks (β) or risk, expected return rate [E(Ri)], conducting correlation tests, plotting the security market line graph, and categorizing stocks as efficient and inefficient based on comparisons between the actual return rate (Ri) and expected return rate [E(Ri)], beta values (β), and comparisons between the risk-free rate (Rf) and expected return rate [E(Ri)]. Based on the analysis results, it is found that 21 company stocks have an average positive actual return rate (Ri), 20 stocks have a beta value (β) greater than 1, 14 stocks have a beta value (β) less than 1, and 7 stocks have a negative beta value (β). There are 26 company stocks with a positive expected return rate [E(Ri)], indicating a strong positive correlation between the expected return rate [E(Ri)] and beta values (β) or risk. Regarding stock categorization, out of the 41 sample companies, 11 stocks are categorized as efficient because their actual return rate (Ri) is greater than the expected return rate [E(Ri)], while 30 stocks are categorized as inefficient due to their actual return rate (Ri) being less than the expected return rate [E(Ri)]. Furthermore, 20 stocks are efficient as they have a beta value (β) greater than 1, 14 stocks are inefficient with a beta value (β) less than 1, and 7 stocks show an inverse relationship with market conditions due to their negative beta value (β). Additionally, 7 stocks are efficient as their expected return rate [E(Ri)] is greater than the risk-free rate (Rf), whereas 34 stocks are inefficient since their expected return rate [E(Ri)] is less than the risk-free rate (Rf).